THE SPECIFICS OF ADOLESCENT CRISIS DURING THE COVID-19 PANDEMIC - Dukanac, Vesna; Ljubomirovic, Natasa; Dukanac, Dusica (HEALTH CARE, 2020)
Introduction/Aim: Adolescents pass through three phases of an accidental crisis: the negation of realdanger, feeling of confusion and chaos with the onset of the first symptoms, a complete depressivebreakdown with a different range of manifestations. The Covid-19 pandemic has become a realchallenge for these patients. The aim of this study is to review and analyze the clinical psychotherapeuticmaterial of the described phases of the passage through the accidental crisis, caused by the Coronaviruspandemic.Methods: Adolescents of different ages are involved. The materials of psychotherapeutic sessions ofadolescents were used in the paper, from different phases of the adolescent crisis. To explain the phaseof negation of real danger, adolescents of the early and central stages of a period of adolescence arepresented. To explain the phase of feelings of confusion and chaos to complete depressive breakdown,adolescents of the late and post adolescent stages of a period of adolescence are presented.Patient presentation: In adolescents, who did not show a problematic passage through thedevelopmental crisis, the accidental crisis of the pandemic leads to the denial of the real danger. In ayounger, twelve-year-old adolescent, at a specific level of functioning, there is a weakened concentrationfor learning. In a slightly older, fifteen-year-old adolescent, the denial of real danger, throughsublimation, goes into altruism. In adolescents with already manifested problematic passage throughthe developmental crisis, the symptoms worsen due to the effect of the superimposed accidental crisiscaused by the pandemic. In adolescents, the middle phase of adolescence, there is a mixture of realsomatic problems with somatization. In the older adolescent, post adolescent phase, with addictiondisease problems, the pandemic provokes irritability and low frustrating tolerance leading to completedepressive breakdown.Conclusion: We can conclude that the superposition of accidental crises always complicates thenormative adolescent crisis, but we emphasize that the manifested psychopathology can be of atransient character. Psychiatric psychotherapeutic interventions are determined in relation to thedegree of threatening or completely manifested decompensation from shorter counseling interventionsto the intensification of deep psychotherapy, with or without adequate drug therapy.
Keywords: adolescent’s crisis, pandemic, Covid-19